Malaysian general election: offence and misconduct of bribery / Ahmad Hafiz Abdul Hair...[et al.] - Abdul Hair, Ahmad Hafiz; Khalid, Akmal Syahmi; Ab. Hadi, Mohd Hakimie; Johan, Zulhakimi (Faculty of Law, 2013)
The topic of our project paper is quite difficult to be conducted, in term of how we obtained the resources for the references. We initially decided to conduct this project paper, due to the fact that there are a lot of allegations on the misconduct of some of the campaigners in order to ensure that the voters in the constituencies vote in favour for the candidates. In spite of the fact that this topic is quite controversial to be discussed, we did try our best to take this challenge as we believe that the topic must not only to be analyzed from the perspective of political view, but it is also important for us to look at it from the perspective of academic analysis. The main reason for this research is to study, especially on judicial approaches relating the problem. We started our research with some reading and analysis on the issue in this topic. It was not as difficult as it ought to be, on the basis of the availability of the sources to be accessed electronically, especially by using online resources. Then, we started to analyze all those information by comparing the cases that we have in Malaysia with the cases decided in United Kingdom. The outcome of the research were then be presented and then were put in the recommendation on how such weaknesses are to be improved